COVID-19 and estimates of actual deaths in Italy. Scenarios for urban planning in Lombardy - Marika Fior; Vassilis Mpampatsikos (Journal of Urban Management, 2021)
This research investigates the direct effects of the Covid-19 pandemic in Italy, focusing on Lombardy, the most affected region by the pandemic both in the first wave of infection (March-April 2020) as well as in the second wave (October-November 2020). We analyzed the data of the death tolls provided by the Italian National Institute of Statistics in April 2020 with the aim to provide reliable estimates and maps of deaths due to Covid-19 at the local scale, and hence better guiding decisions on spatial planning. Firstly, we performed a statistical analysis at the national level, carried out on a region-by-region basis, to compare the total number of deaths in 2020 to the average values of the previous five years. We focused on the last three weeks of March when the lockdown restrictions have been fully applied. We observed that the mortality rate has been much higher than the average recorded in recent years (2015-2019), both in Italy and Lombardy. Additionally, we estimated that the 'excess deaths' in March 2020 are more than fourfold (325% in Italy) the official number of deaths due to Covid-19 reported by the Ministry of Health. This leads to the dramatic consideration that most of the Covid-19-related deaths occurred at home. Lastly, using geo-referenced data by Geographic Information System analysis at the municipality scale, we investigated the Covid-19 effects by grouping the deceased into five age-groups, aiming to map the correlation between geography and population age. Lombardy is a wide region, characterized by various territories, such as mountains, flat landscapes, metropolitan and touristic areas. The Covid-19 pandemic affected each area in a specific way. For each of them, according to the demographic pyramid's reconfiguration, we should assume an urban planning scenario that is place-based, sustainable and resilient.
Keywords: 710; Covid-19; Urban planning; Resilience; Lombardy; Fragility; Urban health